Bioethics Yearbook
VI, 433 p.
Keywords: nology in New Zealand. Angeles Tan Alora reports on the Code of Pharmaceutical Marketmg Practices developed by the Pharmaceutical and Health Care Association of the Philippines. Ruud ter Meulen and his colleagues provide detailed analysis of the Remmelink Commission's report on euthanasia in the Netherlands. Kazumasa Hoshino discusses the fmdings of the Special Committee on Gene Therapy in Japan. As such examples suggest, the activities of many governmental groups and professional advisory bodies, although varied, tend to converge upon a number of especially important issues. If one peruses the index of documents discussed in Volume Four, certain topics are more often the focus of legislation and official concern than others: withholding and withdrawing treatment, access to health care, consent to treatment and experimentation, and issues posed by HIV testing and AIDS. Such a common focus should not be exaggerated, for the discussion of topics is wide-ranging. But that commonality, when in evidence, is also not surprising. It suggests that key issues and concerns in bioethics may be widely shared among modern cultures and societies, for all the distinctiveness of a particular nation's or region's response to them. Issues of informed consent, after all, implicate more fundamental matters of respect for persons and the rights of individuals in the contexts of therapy and research. Issues of access to medical care concretize deeper questions about the nature and scope of a society's welfare obligations to its citizens.